Study on Formulation, in vivo Exposure, and Passive Targeting of Intravenous Itraconazole Nanosuspensions - Yuan, Qi; Wang, Yanling; Song, Rufeng; Hou, Xianqiao; Yu, Keke; Zheng, Jiaojiao; Zhang, Juanmei; Pu, Xiaohui; Han, Jihong; Zong, Lanlan (Frontiers in Pharmacology, 2019)
The pharmacokinetic profile of a drug can be different when delivered as a nanosuspension compared with a true solution, which may in turn affect the therapeutic effect of the drug. The goal of this study was to prepare itraconazole nanosuspensions (ITZ-Nanos) stabilized by an amphipathic polymer, polyethylene glycol-poly(Benzyl aspartic acid ester), by the precipitation-homogenisation, and study the pharmacokinetic curve of the ITZ-Nanos. The particle size and morphology of nanosuspensions were assayed by Zetasizer and field emission scanning electron microscope (SEM), severally. The dissolution profile was evaluated using a paddle method according to Chinese Pharmacopoeia 2015. The level of ITZ in blood and tissues was measured by a HPLC method. The optimized ITZ-Nanos had a mean particle size of 268.1±6.5 nm and the particles were in a rectangular form. The dissolution profile of ITZ-Nanos resemble that of commercial ITZ injections, with nearly 90% ITZ released in the first five minutes. The ITZ-Nanos showed distinct pharmacokinetic properties compared with the commercial ITZ injections, including a reduced beginning drug concentration, enhanced t1/2 and MRT, and increased concentration in the liver, lung and spleen. The ITZ-Nanos can change the in vivo distribution of ITZ and result in passive targeting to the organs with mononuclear phagocyte systems.